2018
DOI: 10.1007/s40618-018-0914-0
|View full text |Cite
|
Sign up to set email alerts
|

High serum osteopontin levels are associated with prevalent fractures and worse lipid profile in post-menopausal women with type 2 diabetes

Abstract: In post-menopausal women with T2DM, OPN might be a useful marker of fracture and worse lipid profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
1
13
0
1
Order By: Relevance
“…For OPG we measured increased serum levels, which confirms a finding by Ostrowska et al [26], although in patients with AN an increased secretion of RANKL, and decreased levels would be expected due to estrogen deficiency [27]. Osteopontin (OPN) is a non-collagenous matrix protein expressed in bone tissue, which is involved in bone remodeling and capable of activating bone resorption [28]. Osteopontin has been associated with increased fracture risk in postmenopausal women, but previous reports on serum levels in subjects with AN are lacking.…”
Section: Discussionsupporting
confidence: 82%
“…For OPG we measured increased serum levels, which confirms a finding by Ostrowska et al [26], although in patients with AN an increased secretion of RANKL, and decreased levels would be expected due to estrogen deficiency [27]. Osteopontin (OPN) is a non-collagenous matrix protein expressed in bone tissue, which is involved in bone remodeling and capable of activating bone resorption [28]. Osteopontin has been associated with increased fracture risk in postmenopausal women, but previous reports on serum levels in subjects with AN are lacking.…”
Section: Discussionsupporting
confidence: 82%
“…Circulating levels of insulin like-growth factor-1 (IGF-1) have also been associated with an increased fracture risk [ 102 104 ], both with prevalent vertebral fractures [ 102 ] and incident fractures [ 104 ]. Also, circulating levels of osteopontin and osteoglycin have been associated with prevalent vertebral fractures and may be novel fracture predictors in T2D [ 105 106 ]. Future fracture predictors in T2D may be measurable in blood; however, further research is needed and until such fracture predictors are established, BMD continue to be the best fracture predictor available.…”
Section: Detection Of Diabetic Bone Diseasementioning
confidence: 99%
“…Our ELISA results showed significantly higher serum levels of OPN and β‐CTX in hip fracture in the elderly compared to healthy controls. Previous studies have shown that a high serum level of OPN results in increased fracture and a worse lipid profile in postmenopausal women with type 2 diabetes . Higher serum levels of OPN are observed in patients with OP and are correlated with the decline of BMD, increase of bone turnover markers, and osteoporotic vertebral fractures .…”
Section: Discussionmentioning
confidence: 95%
“…A recent study reported that OPN is overexpressed in idiopathic hip osteoarthritis and promotes its development . In addition, another study concluded that increased serum levels of OPN are correlated with prevalent fractures in postmenopausal women with type 2 diabetes . As a member of the carboxy‐terminal cross‐linking telopeptide of type I collagen (CTX) family, β‐CTX has been confirmed as a significant marker in bone resorption and formation .…”
Section: Introductionmentioning
confidence: 99%